Diversity and indigenous utilization of bamboo in Xishuangbanna, Yunnan Province, Southwest China - Wang, Kanglin; Hong, L.T.; Rao, V. Ramanatha (Brill Academic Publishers, 2002)
There are more than 100 species of 17 genera of bamboos recorded from Xishuangbanna. The genera Bambusa, Dendrocalamus and Gigantochloa that contain the most species are also common in southeast Asia, hence indicating the similarity of species between these two regions. The other more common species are Indossa, Melocalamus and Phyllostachys. Bamboos of Xishuangbanna are a traditional source of raw materials in the daily life of the many ethnic communities living in the Xishuangbanna area. The various species used for building houses, food, medicine, agricultural tools, handicrafts, cultural and religious activities and horticulture are described briefly in this report.